PENGARUH JUMLAH PRODUKSI, KURS DOLLAR, DAN PERMINTAAN DALAM NEGRI BATUBARA TERHADAP JUMLAH EKSPOR BATUBARA INDONESIA - Rizki, Muhammad Khoiron; Setiawan, Nyoman Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.06.TAHUN.2022, 2022)
The high demand for coal provides an attractive market prospect for Indonesian coal exporters. The purpose of this study was to determine the effect of the Amount of Coal Production, US Dollar Exchange Rate, and Domestic Demand for Coal simultaneously and partially on the Total Indonesian Coal Exports in 2000-2020, and to find out the variables that had a dominant influence on the Total Indonesian Coal Exports in 2000. -2020. This study uses quantitative data in the form of secondary data. Data was collected through non-participant observation methods, namely from books, articles, journals, and reports from related sources or agencies. The analysis technique used is multiple linear regression using time series data from 2000–2020. The results showed that the variables of the amount of production, the US dollar exchange rate, and domestic demand simultaneously had a positive effect on the number of coal exports. Partially the amount of production, the US dollar exchange rate, and domestic demand have a positive effect on the number of coal exports. The variable amount of production has a dominant influence on Indonesian Coal Exports compared to other independent variables, namely the US Dollar Exchange Rate and Domestic Demand.